Description of Total Vitamin D25-Oh in Toddlers and Children With Developmental Disorders - Putri Perdana Jendra Dewi; Adelia Febriyossa; Basuki Rachmad; Apriani Apriani (Riviera Publishing, 2022)
The age of children is a period in which the process of growth and development takes place. The existence of growth and development disorders in children is a serious problem for both developed and developing countries worldwide. The importance of monitoring growth and development requires adequate nutrition and nutrition, one of which is vitamin D. Vitamin D is a prohormone that plays an important role in the absorption of calcium in the intestine and helps harden bones by regulating the availability of calcium in the blood. This study aims to describe Total Vitamin D 25-OH in toddlers and children with growth and developmental disorders. The research sample was determined by purposive sampling technique based on inclusion and exclusion criteria. The research was conducted at Prodia Kramat Clinical Laboratory in March-April 2021. The D 25-OH level was checked from the patient's serum using the DiaSorin Liaison XL tool. Other variables measured to determine vitamin D status are appetite, eating frequency, nutritional adequacy, consumption of vitamin D supplements, outdoor activity, sunbathing, and genetic and environmental risk factors. Data from the examination of total vitamin D 25-OH levels and vitamin D status of the respondents were analyzed descriptively, then displayed in a table and described. The results showed that most respondents who were examined experienced stunting expected growth and development disorders by 76%, with total vitamin D 25-OH status experiencing insufficiency of 53% .